Correlation of Leaf NPK and Leaf Pigments of Coleus atropurpureus L. Benth during Vegetative and Generative Phases - Respita, Intan Annisa; Aziz, Sandra Arifin; Kurniawati, Ani (Department of Agronomy and Horticulture, IPB University, 2019)
Coleus atropurpureus L. Benth is a annual plant that has a distinctive leaf aroma and bitter taste. C. atropurpureus leaves contain phenolic compounds and antioxidants that can capture free radicals; free radicals play an important role in preventing various human diseases. A study was conducted to determine the correlation between leaf position (1st to 4th) at the vegetative and generative phases with leaf pigments, N, P, K, and total flavonoid concentrations. The results showed that leaf chlorophyll a, chlorophyll b, total chlorophyll, carotenoid, anthocyanin, nitrogen, and total flavonoids were higher in the vegetative phase. Therefore, C. atropurpureus is better harvested in the vegetative phase, and the 2nd leaf position can be used as indicator for N, K, pigments and total flavonoid content.